The uneven struggle for bluefields: waterfront transformation in post-socialist Bratislava - Machala, Branislav (Hungarian Geographical Bulletin, 2014)
Waterfront areas are undergoing rapid transformation in many post-socialist cities. This paper focuses on the uneven access to the waterfront in post-socialist Bratislava. We use the bluefield concept of Pinch, P. and Munt, I. (2002). The goal of the paper is to investigate the mechanisms and key forces of waterfront transformation in post-socialist Bratislava in the context of institutional practices, where the role of individual stakeholders and planning are critically evaluated. The limited capacity of post-socialist institutions to mediate and respond to the dynamically increasing demand to waterfronts is highlighted. In the paper two case study areas are investigated with sharply diff erent conditions. In the case of Karlova Ves cove contradictions between the use value and exchange value is demonstrated, leading to a sharp struggle among potential users. The transformation of the second chosen area, Jarovce river branch, demonstrates a power invasion in the area and the illegal privatisation of public areas by ’better off ’ people. The comparison of transformations of these two localities in a relatively similar time frame, provides a picture about the uneven struggle for access. Both discussed examples draw att ention to persisting institutional adaptation and the fragile de facto position of the municipality in urban development.